2012
DOI: 10.1007/s10856-012-4734-z
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of mesoporous bioactive glass/polycaprolactone nanofibrous matrix for bone tissues engineering

Abstract: A polycaprolactone (PCL) nanofibrous composite matrix having mesoporous bioactive glass nanoparticles (MBG) was fabricated using the electrospinning method, and the microstructural, physical and biological properties of the composite matrix were characterized. The fiber diameters of PCL, 5 % MBG/PCL (5 M-PCL) and 10 % MBG/PCL (10 M-PCL) were 575 ± 162 nm, 312 ± 134 nm and 321 ± 144 nm, respectively. The bioactivity of the composite matrix was evaluated by soaking the matrix in 1.5× simulated body fluid; the MB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 42 publications
3
48
0
1
Order By: Relevance
“…Enhanced attachment, proliferation, and early differentiation of hMSCs on the SMC/ PHBHHx may result from the direct contact of seeded cells with the SMC particles exposed on the scaffold surface, which might provide cell adhesion sites with better cellular adherence and spreading to stimulate cell proliferation and osteogenic differentiation. 31,32 In addition, SMC/PHBHHx has a higher surface area than pure PHBHHx matrix; most researchers believe that this may promote cell growth more efficiently than a bulk substrate. We also determined that the percentage of hMSCs attached on the SMC/PHBHHx composite with 20 wt% SMC was higher than on pure PHBHHx.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced attachment, proliferation, and early differentiation of hMSCs on the SMC/ PHBHHx may result from the direct contact of seeded cells with the SMC particles exposed on the scaffold surface, which might provide cell adhesion sites with better cellular adherence and spreading to stimulate cell proliferation and osteogenic differentiation. 31,32 In addition, SMC/PHBHHx has a higher surface area than pure PHBHHx matrix; most researchers believe that this may promote cell growth more efficiently than a bulk substrate. We also determined that the percentage of hMSCs attached on the SMC/PHBHHx composite with 20 wt% SMC was higher than on pure PHBHHx.…”
Section: Discussionmentioning
confidence: 99%
“…the polymer and inorganic particles, the BG loading up to 15 wt% led to the improvement of the tensile strength however simultaneously to a decrease in strain [71].…”
Section: Electrospun Composite Fibersmentioning
confidence: 98%
“…Kouhi et al [70] and Lin et al [71] both fabricated sol-gel-derived bioactive glass/PCL fibrous scaffolds through electrospinning from a solution of PCL and glass nanoparticles. The study of Kouhi et al showed that bioactivity and cell differentiation activity were significantly improved due to the nanosized bioactive glass addition.…”
Section: Electrospun Composite Fibersmentioning
confidence: 99%
“…7) with controlled simvastatin-releasing property. Due to the suitable physical interactions between the polymer and inorganic particles, the BG loading up to 15 wt% led to the improvement of the tensile strength however simultaneously to a decrease in strain [71].…”
Section: Electrospun Composite Fibersmentioning
confidence: 99%
See 1 more Smart Citation